pH-responsive poly(aspartic acid) hydrogel-coated magnetite nanoparticles for biomedical applications - Vega-Chacón, Jaime [UNESP]; Arbeláez, María Isabel Amaya [UNESP]; Jorge, Janaina Habib [UNESP]; Marques, Rodrigo Fernando C. [UNESP]; Jafelicci, Miguel [UNESP] (Elsevier, 2017)
A novel multifunctional nanosystem formed by magnetite nanoparticles coated with pH-responsive poly(aspartic acid) hydrogel was developed. Magnetite nanoparticles (Fe3O4) have been intensively investigated for biomedical applications due to their magnetic properties and dimensions similar to the biostructures. Poly(aspartic acid) is a water-soluble, biodegradable and biocompatible polymer, which features makes it a potential candidate for biomedical applications. The nanoparticles surface modification was carried out by crosslinking polysuccinimide on the magnetite nanoparticles surface and hydrolyzing the succinimide units in mild alkaline medium to obtain the magnetic poly(aspartic acid) hydrogel. The surface modification in each step was confirmed by DRIFTS, TEM and zeta potential measurements. The hydrodynamic diameter of the nanosystems decreases as the pH value decreases. The nanosystems showed high colloidal stability in water and no cytotoxicity was detected, which make these nanosystems suitable for biomedical applications.
Keywords: Hydrogel; Magnetite nanoparticles; pH-responsive; Poly(aspartic acid)